2011
DOI: 10.1111/j.1600-051x.2011.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss in aggressive periodontitis after active periodontal therapy: patient-related and tooth-related prognostic factors

Abstract: Baseline bone loss, abutment status, tooth location, and type as well as time of follow-up and educational status were detected as prognostic factors for tooth loss during SPT in patients with AgP at tooth level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 34 publications
(51 reference statements)
7
78
3
5
Order By: Relevance
“…A longitudinal study found that there is no contribution from socioeconomic differences in attitudes toward tooth loss and dental care 31 . Conversely, other studies demonstrated that lower socioeconomic status is associated with decreased utilization of dental care services, worse oral health, and increased tooth loss compared with higher socioeconomic groups 32‐34 . Interestingly, the current study reveals that an individual's socioeconomic status is not significantly correlated to the prognosis of root‐resected molars (Table 4) but plays an important role in the therapeutic decision‐making process (Table 2).…”
Section: Discussioncontrasting
confidence: 51%
“…A longitudinal study found that there is no contribution from socioeconomic differences in attitudes toward tooth loss and dental care 31 . Conversely, other studies demonstrated that lower socioeconomic status is associated with decreased utilization of dental care services, worse oral health, and increased tooth loss compared with higher socioeconomic groups 32‐34 . Interestingly, the current study reveals that an individual's socioeconomic status is not significantly correlated to the prognosis of root‐resected molars (Table 4) but plays an important role in the therapeutic decision‐making process (Table 2).…”
Section: Discussioncontrasting
confidence: 51%
“…This combination is described as the basis and the ‘gold standard’ of periodontal treatment. When applied consistently, periodontal health can be maintained in long term , disclosing in the latter study a time frame of up to 30 years of SPT. In this review, three studies reported data on PPD changes .…”
Section: Discussionmentioning
confidence: 88%
“…However, many researchers consider the rate of tooth loss to be an effective evaluation of periodontal treatment [30,31]. Further research should be performed using novel methods that exclude the influence of the dentist.…”
Section: Discussionmentioning
confidence: 99%